Contamination Mitigating Polymeric Coatings for Extreme Environments - Wohl, Christopher J.; Berry, Douglas H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume provides perspectives on the approaches, mechanisms, test methods, durability considerations, and environmental concerns for contamination mitigating coatings and polymers with emphasis on their use in more extreme aerospace and marine terrestrial environments. Parts of the Volume are devoted to application of biomimetics to contamination mitigation polymeric coatings, low ice adhesion surfaces, insect residue adhesion resistance coatings, and marine biofouling mitigation materials. By juxtaposing ice insect, and marine mitigation approaches, researchers and users may more easily identify threads of similarity that will assist in future developments and potential applications in these areas. The volume is of interest to chemists and material scientists in providing awareness of both the need for efficacy in mitigating contamination and for appropriate coating durability; to physicists in providing better understanding of the interaction between the contaminant, the coated surface, and the surrounding environment; and to engineers in describing the need for better scale-up tests between laboratory and field environments.
Aerospace and Marine Environments as Design Spaces for Contamination-Mitigating Polymeric Coatings -- Part I. Application of Biomimetics to Contamination-Mitigating Coatings -- Influence of Topography on Adhesion and Bioadhesion -- Part II. Ice Contamination-Mitigating Coatings -- Use of Liquid Ad(ab)sorbing Surfaces for Anti-icing Applications -- Ice Adhesion on Superhydrophobic Coatings in an Icing Wind Tunnel -- Icephobicity: Definition and Measurement Regarding Atmospheric Icing -- Development and Testing of Icephobic Materials: Lessons Learned from Fraunhofer IFAM -- Ice Release Coatings of High Durability for Aerospace Applications -- Antifogging and Frost-resisting Polymeric Surfaces -- Part III. Insect Contamination-Mitigation Coatings -- An Overview of Insect Residue Accretion and Mitigation Strategies on Aerodynamic Surfaces -- The Physics of Insect Impact and Residue Expansion -- Laboratory Investigation into Anti-contamination Coatings for Mitigating Insect Contamination with Application to Laminar Flow Technology -- Insect Abatement on Lubricious, Low Adhesion Polymer Coatings Measured with an Insect Impact Testing System -- Requirements, Test Strategies and Evaluation of Anti-contamination and Easy-to-clean Surfaces and New Approaches for Development -- Part IV. Biofouling-Mitigation Coatings -- Candy and Poisons: Fouling Management with Pharmacophore Coatings -- Unique Silicone-epoxy Coatings for both Fouling- and Drag-resistance in Abrasive Environments.
Keywords: Polymers; Coatings; Tribology; Corrosion and anti-corrosives.; Polymers; Coatings; Tribology; Corrosion